Culture Shock and Communication Adaptation Among Students in the Fo Guang Environment in Indonesia - Laudia Sari; Sudarto Sudarto; Widia Darma (Presscience, 2026)
This study explores culture shock and communication adaptation among students in the Indonesian context of Fo Guang Shan, a transnational Buddhist organization grounded in Humanistic Buddhism. Using an observational research design and thematic analysis based on Kim’s Integrative Communication Theory, the study examines students’ daily interactions and participation in religious and educational activities. The findings show that culture shock emerges through differences in language, symbols, nonverbal cues, and interaction styles, especially in the early stages of engagement. Communication adaptation develops gradually through awareness of cultural differences, experimentation with local norms, and growing confidence supported by community participation. The Fo Guang Shan environment plays a dual role, initially creating communicative tension but later functioning as a supportive learning space that accelerates students’ social integration. The study contributes to applied intercultural communication by showing how culture shock in religious settings can become a learning resource and by offering practical insights for designing context-specific intercultural orientation and training programs.